Strategy for technology energy selection to achieve coal value added in PT. Bukit Asam (Persero), Tbk., - Peni Rostiarti; Eddy Ibrahim; Taufik Toha (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2017)
The role of coal in providing national energy has already increased nowadays, and still taking an important subject. Government obligation to support added value is not really encourage industry player to applied technology energy that has been developed widenly in South Africa, China and others developing country. The scope of this research is technology energy for coal diversification, such as Coal Upgrading, Coal Gasification, Coal Liquefaction, Coal Water Mixture, and applied Coal Bed Methane Technology that extract gas methane from the pore of coal. The purpose of this research is to estimate coal resources, quality range and to select technology energy that can be potentially develop in PT. Bukit Asam (Persero), Tbk. Coal Resources and coal quality in each mining licences area becomes the basic strength for developing technology energy as part of SWOT Analysis. Based on the SWOT Analysis from 5 technology energy then the scope limited into 3 highest technology energy that is Coal Gasification, Coal Liquefaction and Coal Bed Methane as the most potential technology energy to develop in PT. Bukit Asam (Persero), Tbk.